Communication in the instructional design of a technical vocational and livelihood course at a senior high school in Los Banos, Laguna, Philippines - Velasco, Maria Dominique C.; Tirol, Maria Stella C. (2017)
Research about communication in instructional systems design has been overlooked in previous studies in the field of educational communication. To address the gap, this study analyzed the communication process that took place in each stage of the instructional design for a technical vocational and livelihood (TVL) track on bread and pastry production (BPP). Bread and pastry production is one of the specialized courses offered in the TVL track for K-12 students in the Philippines.

Interviews with key persons involved in the instructional design of the BPP course were conducted. Pre- and post-tests were used to quantify student learning that occurred, while teacher clarify report questionnaire and focus group discussion were used to measure classroom understanding.

The respondents and key informants of the study showed characteristics reflective of the general population in the country. The communication process involved participants from the government and the school who used a combination of channels to exchange information about bread and pastry production in a two-way interaction. Decision-making focused on key government and school representatives with decisions arrived at through meetings and consultations. Evaluation results showed that the teacher was able to effectively communicate the contents of the lesson and carry out classroom processes. The study recommended policies relevant to improve communication and enhance three phases of instructional design.
Keywords: Instructional design; Instructional designs -- Communication; Technical vocational course